Atypical presentation of medication-related osteonecrosis of the jaw in a young male patient undergoing chemotherapy for acute lymphoblastic leukemia - Ferit Bayram; Sardar Fattahzade; Ant Uzay; Yaşar Özkan (Oral Oncology Reports)
This case report aims to highlight the importance of close oral monitoring before and during chemotherapy in patients with B-cell acute lymphoblastic leukemia (B-ALL) to prevent medication-related osteonecrosis of the jaw (MRONJ). A 22-year-old male patient diagnosed with B-ALL who developed MRONJ during chemotherapy, despite not receiving bisphosphonates or denosumab, was presented. The patient's medical history, treatment regimen, clinical examination findings, and treatment outcomes were reported. The patient developed maxillofacial cellulitis during chemotherapy, leading to a diagnosis of stage 3 MRONJ. Conservative treatment was initiated, resulting in the reversion of the disease to stage 1 and stabilization of the progression. The patient achieved remission and underwent prophylactic cranial radiotherapy. This case report presents a unique case of MRONJ in a young patient without prior use of antiresorptive agents or denosumab. It highlights the need for close oral monitoring in patients with B-ALL before and during chemotherapy, as MRONJ can develop in the absence of these medications.